2014
DOI: 10.1371/journal.pone.0101182
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sites of STAT3 Action in the Female Reproductive Tract through Conditional Gene Deletion

Abstract: The STAT3 transcription factor is a pleiotropic transducer of signalling by hormones, growth factors and cytokines that has been identified in the female reproductive tract from oocytes and granulosa cells of the ovary to uterine epithelial and stromal cells. In the present study we used transgenic models to investigate the importance of STAT3 for reproductive performance in these different tissues. The Cre-LoxP system was used to delete STAT3 in oocytes by crossing Stat3fl/fl with Zp3-cre+ mice, or in ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Which other factors are involved in the expression of MCP1 in the POAT following estradiol administration? It is known that STAT3 is both an important transcription factor that controls adipose tissue (Richard & Stephens 2014) and reproductive functions (Robker et al 2014). Also, its interaction with the NFKB inflammatory pathway was documented (Sarkö zi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Which other factors are involved in the expression of MCP1 in the POAT following estradiol administration? It is known that STAT3 is both an important transcription factor that controls adipose tissue (Richard & Stephens 2014) and reproductive functions (Robker et al 2014). Also, its interaction with the NFKB inflammatory pathway was documented (Sarkö zi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…p-STAT3 is known to translocate to the nucleus and increase proliferation-associated gene expression (Annerén 2008, Hiraoka et al 2016. Accordingly, reduced p-STAT3 can induce infertility (Sun et al 2013, Robker et al 2014. Interestingly, p-STAT3 was not decreased at 8 h after E 2 + P 4 treatment in CD31 −/− mice ( Fig.…”
Section: Discussionmentioning
confidence: 88%
“…50,51 The uterine-specific knockout of a downstream target of Gp130 and the LIFR; that is, a signal transducer and activator of transcription 3 (Stat3) also caused the failure of implantation. 51 The epithelium-specific deletion of Stat3 (Wnt7 Cre/+ ; Stat3 flox/ flox ) also was reported recently to show implantation failure, followed by the downregulation of fibroblast growth factors (FGFs) and a cell-cell adhesion protein, cadherin, 52 whereas a stromalspecific deletion (Amhr2 Cre/+ ; Stat3 flox/flox ) simply showed the phenotype with a decreased number of pups, 53 suggesting that the epithelial LIF signaling pathway is indispensable for implantation via FGF signaling. In humans, it was reported that a slight increase in LIF expression was observed at the endometrium before implantation 54 and some clinical studies demonstrated that the LIF expression around the time point of implantation was higher in fertile women, compared to infertile women.…”
Section: Estrogen-dependent Signalingmentioning
confidence: 97%
“…In addition, Wnt7a Cre and Amhr2 Cre transgenic mice were used for epithelial‐specific and SC‐specific deletion, respectively . The deletion of Wnt7a or Amhr2 itself caused a failure of the reproductive organs, suggesting that the phenotype of knockout mice with infertility might be a secondary effect.…”
Section: Outstanding Issuesmentioning
confidence: 99%
See 1 more Smart Citation